An investigation into the stress relieving properties of Sutherlandia frutescens : inhibition of steroidogenic cytochrome P450 enzymes - Prevoo, Desiree (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2005.